Pengaruh Ekstrakurikuler Rohani Islam (Rohis) dan Motivasi Belajar terhadap Hasil Belajar PAI (Studi di SMP Negeri Sungai Penuh - saflidarti, deni - (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
This research examines Rohis' extracurricular activities and learning motivation as support in the learning process which influences PAI learning outcomes. The sample in this study was 301 students at SMPN Sungai Banyak. The method used is quantitative and data collection techniques use questionnaires. This research reveals how much influence Rohis extracurriculars and learning motivation have on PAI learning outcomes by analyzing the results of student questionnaires. The results of this research show that Rohis' extracurricular contribution influences learning outcomes by 13.4%, and learning motivation influences learning outcomes by 39.8%, and Rohis extracurriculars and learning motivation influence learning outcomes together by 41.4%.